FINANCING RISK IN ISLAMIC BANKING BEFORE AND DURING THE COVID-19 PANDEMIC - Mardhiyaturrositaningsih (IAIN Lhokseumawe, 2022)
This study aims to identify the risk of financing in Islamic Banks. Financing risk assessment is divided into two categories, financing based on contract and financing based on usage. This study uses a comparative analysis method to identify differences in financing risks in the period before and during the Covid-19 pandemic. The results of the study show that there are six differences in financing risks based on the contract period before and during the Covid-19 pandemic. The risk of financing based on use shows that there is no difference in the risk of financing investment for MSMEs before and during the Covid-19 pandemic. Meanwhile, the difference can be seen in the risk of working capital financing for MSMEs, working capital financing for Non-MSMEs, the risk of investment financing for Non-MSMEs and the risk of consumptive financing. These results indicate that Islamic bank financing is responding to the Covid-19 pandemic with changes in financing risk. Banks need to manage financing with the aim of increasing financing not increasing risk.